(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: the verb "to be" is a fundamental part of language, serving as the copula that connects a subject to its complement. This article explores the importance and usage of the "to be" verb in both the English and Uzbek languages. It examines how the verb functions grammatically, the nuances in its application, and the ways in which it shapes the structure and expression of these two languages.